2021
DOI: 10.3390/ma14237137
|View full text |Cite
|
Sign up to set email alerts
|

Screen Printed Copper and Tantalum Modified Potassium Sodium Niobate Thick Films on Platinized Alumina Substrates

Abstract: We show how sintering in different atmospheres affects the structural, microstructural, and functional properties of ~30 μm thick films of K0.5Na0.5NbO3 (KNN) modified with 0.38 mol% K5.4Cu1.3Ta10O29 and 1 mol% CuO. The films were screen printed on platinized alumina substrates and sintered at 1100 °C in oxygen or in air with or without the packing powder (PP). The films have a preferential crystallographic orientation of the monoclinic perovskite phase in the [100] and [−101] directions. Sintering in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The intensities of the (100) and (010) peaks at 2 Theta ~22 degrees and the intensities of the (−101), (101), and (110) peaks at 2 Theta ~32 degrees did not match the intensities for the bulk ceramics (Figure 6b,c). It has been reported that the KNN-based thick films on alumina have a preferential crystallographic orientation in the [100] and [−101] directions, which is related to the stresses developed in the thick films due to the mismatch between the thermal expansion of the KNN and the alumina substrate and the phase transition of the KNN [15,16,28]. Alumina has a thermal expansion coefficient (TEC) of 8 × 10 −6 K −1 , while the TEC of KNN is lower, namely, 7.5 × 10 −6 K −1 , 4.35 × 10 −6 K −1 , and 2.96 × 10 −6 K −1 for the cubic, tetragonal, and monoclinic phases, respectively [29].…”
Section: Resultsmentioning
confidence: 99%
“…The intensities of the (100) and (010) peaks at 2 Theta ~22 degrees and the intensities of the (−101), (101), and (110) peaks at 2 Theta ~32 degrees did not match the intensities for the bulk ceramics (Figure 6b,c). It has been reported that the KNN-based thick films on alumina have a preferential crystallographic orientation in the [100] and [−101] directions, which is related to the stresses developed in the thick films due to the mismatch between the thermal expansion of the KNN and the alumina substrate and the phase transition of the KNN [15,16,28]. Alumina has a thermal expansion coefficient (TEC) of 8 × 10 −6 K −1 , while the TEC of KNN is lower, namely, 7.5 × 10 −6 K −1 , 4.35 × 10 −6 K −1 , and 2.96 × 10 −6 K −1 for the cubic, tetragonal, and monoclinic phases, respectively [29].…”
Section: Resultsmentioning
confidence: 99%